2014
DOI: 10.1101/cshperspect.a015354
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis

Abstract: Psoriasis is a common chronic inflammatory skin disease with a spectrum of clinical phenotypes and results from the interplay of genetic, environmental, and immunological factors. Four decades of clinical and basic research on psoriasis have elucidated many of the pathogenic mechanisms underlying disease and paved the way to effective targeted therapies. Here, we review this progress and identify future directions of study that are supported by a more integrative research approach and aim at further improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
220
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(230 citation statements)
references
References 180 publications
(227 reference statements)
5
220
0
5
Order By: Relevance
“…A compelling and recent example is provided by a study in which nociceptors were shown to modulate the phenotype of dermal DCs in a mouse model of psoriasis 73 . Psoriasis is an immune-mediated inflammatory disease of the skin characterized by epidermal hyperplasia and immune infiltration, in which both innate and adaptive immune cells are thought to have a crucial role 146 . Psoriasis can be modelled in rodents by repeated topical application of imiquimod, a potent immune activator, which leads to the formation of skin lesions resembling human psoriasis 147,148 .…”
Section: Modulated Effects Refsmentioning
confidence: 99%
“…A compelling and recent example is provided by a study in which nociceptors were shown to modulate the phenotype of dermal DCs in a mouse model of psoriasis 73 . Psoriasis is an immune-mediated inflammatory disease of the skin characterized by epidermal hyperplasia and immune infiltration, in which both innate and adaptive immune cells are thought to have a crucial role 146 . Psoriasis can be modelled in rodents by repeated topical application of imiquimod, a potent immune activator, which leads to the formation of skin lesions resembling human psoriasis 147,148 .…”
Section: Modulated Effects Refsmentioning
confidence: 99%
“…One of the best-characterized psoriasis initiation mechanisms is the antimicrobial peptide LL-37-DNA/RNA complex resulted from infection or physical trauma (Di Meglio et al, 2014), which induces inflammation, but how to initiate and develop psoriasis remains unknown. As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two closely related G protein-coupled receptors (PKR1 and PKR2)mediate signal transduction of PKs (Negri et al, 2004, Shojaei et al, 2008). Psoriasis, a chronic cutaneous disorder with a spectrum of clinical phenotypes including red, scaly and well-demarcated skin lesions formed by hyperproliferation of epidermal keratinocytes (KC), affects approximately 1–3% of the worldwide population (Baliwag et al, 2015, Di Meglio et al, 2014, Gottlieb, 2005, Nestle et al, 2009). Besides causing ecological burdens, psoriasis produces a severe psychosocial burden such as anxiety, depression, and perceived stress, therefore significantly impairs the quality of patients' life (Gupta et al, 2015, Tohid et al, 2016, Villasenor-Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis is a chronic inflammatory skin disease characterized by increased infiltration of IFNγ-producing Th1 cells as well as IL-17A-producing Th17 cells in the lesional plaques [26]. A model of psoriasis initiation involving the antimicrobial peptide LL-37 and IFNα has been suggested [27,28].…”
Section: Discussionmentioning
confidence: 99%